The fleet system and the troubled shipping institutions in the Portuguese Atlantic (seventeenth and eighteenth centuries). - Souza Melo, Felipe (Colonial Latin American Review, 2023)
Improvements in shipping productivity, resulting from increased maritime safety, are considered essential factors to explain commercial growth in long-distance trade between the seventeenth and nineteenth centuries. However, this article points out that for more than a century, the routes between Portugal and the ports of Brazil were unsafe. The fleet system was the solution found to overcome pirates and privateers. This transport system created a series of problems, though. This article shows how weather conditions, infrastructure problems regarding port facilities, the distances from the port of Recife to sugar mills, and disagreements between shippers, merchants, and sugar mill owners hampered shipping and how they had some negative implications for traders. The fleets generated stocks of sugar in the colony and lengthened the payback period on investments made by merchants in Portugal. These problems disappeared with the end of the fleet system in 1762/1766. Still, others emerged, such as the regulation of freight rates in 1751 and 1766, the decline in shipping productivity throughout the second half of the eighteenth century, and the wars from the 1790s onwards. I argue that shipping in the Portuguese Atlantic was constantly hampered but that this did not prevent commercial growth from occurring.